Chemical attack on concrete containing a high volume of crumb rubber as a partial replacement for fine aggregate in engineered cementitious composite (ECC) - Alaloul, W.S. (Canadian Science Publishing, 2022)
Today, scrap tire is disposed of by open burning which harms the environment. To reduce the wastage of the resource, a sustainable approach is needed to dispose of the waste tire as a partial replacement of the fine aggregate in concrete mixes. This research has been conducted with a focus on the chemical attack of an engineered cementitious composite (ECC) containing a high volume of crumb rubber in terms of durability, behaviour, and comparison with conventional concrete. Two variables have been considered in developing rubberized ECC mixtures, that is, the amount of crumb rubber as a replacement for fine aggregate by volume of 0â30 and PVA fibres by volume of 0â2 to cementitious materials. The resistance properties of ECC incorporating crumb rubber were investigated for 13 different variable combinations developed using response surface methodology (RSM). The experimental results revealed that the presence of crumb rubber in the ECC matrix enhanced the resistance of the ECC in both acidic and sulphate environments. It was also revealed that by incorporating 15 crumb rubber, the loss of compressive strength significantly reduced from 38 to 15. Â© 2022, Canadian Science Publishing. All rights reserved.